2011
DOI: 10.1002/jmr.1121
|View full text |Cite
|
Sign up to set email alerts
|

Hapten–antibody recognition studies in competitive immunoassay of α‐zearalanol analogs by computational chemistry and Pearson Correlation analysis

Abstract: The molecular recognition of hapten-antibody is a fundamental event in competitive immunoassay, which guarantees the sensitivity and specificity of immunoassay for the detection of haptens. The aim of this study is to investigate the correlation between binding ability of one monoclonal antibody, 1H9B4, recognizing and the molecular aspects of α-zearalanol analogs. The mouse-derived monoclonal antibody was produced by using α-zearalanol conjugated to bovine serum albumin as an immunogen. The antibody recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Group 4 showed a significant increase of CASP9 and CYCS , this found was already supported by at least another group that reported same results associated with significant increases in ALT and AFP levels 24. The indirect markers of fibrosis reflect alterations in hepatic function.…”
Section: Discussionsupporting
confidence: 64%
“…Group 4 showed a significant increase of CASP9 and CYCS , this found was already supported by at least another group that reported same results associated with significant increases in ALT and AFP levels 24. The indirect markers of fibrosis reflect alterations in hepatic function.…”
Section: Discussionsupporting
confidence: 64%
“…We concluded that the sulfonic acid groups had strong electron-withdrawing ability, and the absence of the sodium sulfonates could cause the charge distribution of hapten derivatives to significantly differ from that of the tartrazine molecule. However, the charge distribution is crucial for recognition of the antigens by the major histocompatibility complex (MHC), and this has a major influence on the production of antibodies [26,27]. This demonstrates that the sulfonic acid groups of tartrazine play an irreplaceable role in the induction of specific antibody generation, and should be retained in the process of hapten design and synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the computational simulation was employed to investigate these effects in theory. If the charge distribution of hapten derivatives is similar to the target, the antibodies produced will be more specific (Wang, Luo, Cheng, Zhang, & Shen, 2011;Xu, Shen, et al, 2009). The results of charge distribution of atoms in Sudan I and three related hapten derivatives are shown in Figure 3.…”
Section: Food and Agricultural Immunology 19mentioning
confidence: 96%